Nitrogen Removal by Anammox Biofilm Column Reactor at Moderately Low Temperature - Tuty Emilia Agustina; Novia Novia; Gusti Diansyah; Michihiko Ike; Satoshi Soda (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2017)
The anaerobic ammonium oxidation (anammox) as a new biological approach for nitrogen removal has been considered to be more cost-effective compared with the combination of nitrification and denitrification process. However, the anammox bioreactors are mostly explored at high temperature (>300C) in which temperature controlling system is fully required. This research was intended to develop and to apply anammox process for high nitrogen concentration removal at ambient temperature used for treating wastewater in tropical countries. An up-flow biofilm column reactor, which the upper part constructed with a porous polyester non-woven fabric material as a carrier to attach the anammox bacteria was operated without heating system. A maximum nitrogen removal rate (NRR) of 1.05 kg-N m3 d-1 was reached in the operation days of 178 with a Total Nitrogen (TN) removal efficiency of 74%. This showed the biofilm column anammox reactor was successfully applied to moderate high nitrogen removal from synthetic wastewater at moderately low temperature. Keywords: Anammox, biofilm column reactor, ambient temperature, nitrogen removal